Structural, elastic, electronic, optical and thermoelectric properties of the Zintl-phase Ae3AlAs3 (Ae = Sr, Ba) - Benahmed, A.; Bouhemadou, Abdelmadjid; Alqarni, Bander; Guechi, N.; Al-Douri, Yarub; Khenata, Rabah; Bin-Omran, Saad (Taylor & Francis, 2018)
First-principles calculations were performed to investigate the structural, elastic, electronic, optical and thermoelectric properties of the Zintl-phase Ae3AlAs3 (Ae = Sr, Ba) using two complementary approaches based on density functional theory. The pseudopotential plane-wave method was used to explore the structural and elastic properties whereas the full-potential linearised augmented plane wave approach was used to study the structural, electronic, optical and thermoelectric properties. The calculated structural parameters are in good consistency with the corresponding measured ones. The single-crystal and polycrystalline elastic constants and related properties were examined in details. The electronic properties, including energy band dispersions, density of states and charge-carrier effective masses, were computed using Tran-Blaha modified Becke-Johnson functional for the exchange-correlation potential. It is found that both studied compounds are direct band gap semiconductors. Frequency-dependence of the linear optical functions were predicted for a wide photon energy range up to 15 eV. Charge carrier concentration and temperature dependences of the basic parameters of the thermoelectric properties were explored using the semi-classical Boltzmann transport model. Our calculations unveil that the studied compounds are characterised by a high thermopower for both carriers, especially the p-type conduction is more favourable.